2014
DOI: 10.1007/s12640-014-9484-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Alcohol Exposure Affects the Cell Components Involved in Membrane Traffic in Neuronal Dendrites

Abstract: The specific traffic of the membrane components in neurons is a major requirement to establish and maintain neuronal domains-the axonal and the somatodendritic domains-and their polarized morphology. Unlike axons, dendrites contain membranous organelles, which are involved in the secretory pathway, including the endoplasmic reticulum, the Golgi apparatus and post-Golgi apparatus carriers, the cytoskeleton, and plasma membrane. A variety of molecules and factors are also involved in this process. Previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 88 publications
2
14
0
Order By: Relevance
“…Dissociation of HSPA5 during ER stress allows ATF6 to be transported to the Golgi (Shen et al, 2002). Chronic exposure to moderate levels of ethanol in neurons ( in vitro ) increases the levels of HSPA5 (Romero et al, 2015). Hspa5 expression is also altered by chronic ethanol consumption in rats (Bell et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Dissociation of HSPA5 during ER stress allows ATF6 to be transported to the Golgi (Shen et al, 2002). Chronic exposure to moderate levels of ethanol in neurons ( in vitro ) increases the levels of HSPA5 (Romero et al, 2015). Hspa5 expression is also altered by chronic ethanol consumption in rats (Bell et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In response to stress, including exposure of cytotoxic agents, the compact Golgi structure can undergo remodeling characterized by varying degrees of scattering and unstacking [5][6][7][8][9][10]. Multiple studies have demonstrated that in hepatocytes, ethanol (EtOH) administration and it's subsequent metabolism have the ability to alter the structure of the Golgi [11][12][13].…”
Section: Of 17mentioning
confidence: 99%
“…Cultured primary cortical neurons were prepared from cerebral hemispheres of 16-day-old fetal Sprague-Dawley rats. Hemispheres were dissected, mechanically dissociated and plated in polylysine coated dishes (Price and Brewer 2001;Romero et al 2013Romero et al , 2015. Cells were cultured in the Neurobasal medium supplemented with B27 and Glutamax (Price and Brewer 2001).…”
Section: Primary Culture Of Neurons and Alcohol Treatmentmentioning
confidence: 99%
“…These ethanol concentrations are equivalent to blood levels reported in pregnant chronic drinkers and are considered to correspond to moderate alcohol consumption (Eckardt et al 1998). The concentration of ethanol in the medium was determined using a kit from Sigma-Aldrich (nicotinamide adenine dinucleotide-alcohol dehydrogenase Reagent Multiple Test Vial N7160) and ethanol evaporation was minimized as previously described (Romero et al 2015). Cell viability was determined by the trypan blue exclusion test.…”
Section: Primary Culture Of Neurons and Alcohol Treatmentmentioning
confidence: 99%